Questioning the “prototype dwellings” in the framework of Cyprus traditional architecture - Günçe, Kağan; Ertürk, Zafer; Ertürk. Sevinç (Elsevier, 2008)
As one of the basic narratives of culture, traditional residential architecture is an important value, indicating its relationship with its environment. Due to this, the continuity of culture in rural areas is closely related with the sustainability of traditional residential architecture. Cyprus is a Mediterranean island, which has managed to sustain her rich cultural heritage against the many economical, socio-cultural and political changes she has gone through. There is a need for new dwellings in rural areas and this demand is increasing rapidly. In these areas which are physical environments where sustainability can be maintained easily, the Social Housing Department of the North Cyprus Government has made several studies for the proposal of prototype house plans’ as a solution to the above mentioned problem of a need for housing and the prevention of migration to cities. However, upon analysing the architecture of traditional dwellings; and the life-styles of the people who live in these rural areas, it has been observed that these projects, with incomprehensible, strict and totalitarian design principles, are incompatible with local culture and conditions. It is suggested that there is a need for an appropriate environment for the continuation of the life-style that is natural to the people that live within them. On the contrary, these projects form the basis of a step towards a monotonous settlement development which does not respect either the values of traditional architecture or local identities. It is extremely important that the correct steps are taken for both the conservation of the existing physical environment and for handling the issues of new settlement developments in relation to production relationships and cultural sustainability. The main aim of this paper is to draw attention to the traditional design principles that can be re-interpreted in the proposed ‘prototyped dwellings’ in North Cyprus. In order to achieve this aim, a case study, based on observations, literature survey and site survey techniques has been carried out.
Keywords: Culture values; Built environment; Cyprus traditional architecture; Prototype dwellings; Traditional Architecture; Dwelling; Cyprus